Finding a way with words: Delphi study to develop a discussion prompt list for paediatric palliative care. (March 2020) - Ekberg, Stuart; Herbert, Anthony; Johns, Kristi; Tarrant, Gabrielle; Sansone, Holly; Yates, Patsy; Danby, Susan; Bradford, Natalie K
Background: Effective communication is a cornerstone of quality paediatric palliative care. Families report struggling, however, to know what to discuss, with whom, and when. Although question prompt lists exist for adult palliative care, they do not suit the unique circumstances of paediatric palliative care. Aim: To develop a prompt list suitable for paediatric palliative care. Design: Underpinned by Delphi methodology, a six-phase procedure was adopted: (1) drafting items based on the findings of a literature review, (2) condensing the list of items based on group discussion, (3) refining items based on a survey of expert healthcare professionals, (4) additional refining of items based on another survey of professionals, (5) further refining of items based on cognitive interviews with family members, and (6) final review by healthcare professional and family member groups. Participants: Three participant groups were involved during various phases: (1) members of an Australasian paediatric palliative care national reference group, (2) healthcare professionals associated with a local paediatric palliative care service, and (3) family members who were users of the same local service. Results: Through multi-phase consultation across participant groups, the draft question prompt list was refined progressively to 28 items, split across two booklets to allow end-of-life items to be provided separately, and reconceptualised as a discussion prompt list rather than a question prompt list. Conclusion: By involving representatives of major stakeholder groups, this study has facilitated the design of a prompt list suited to the circumstances of paediatric palliative care. Future research should trial the effectiveness of this resource.